2017
DOI: 10.1515/mammalia-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Home range of a male jaguar spatially associated with the landfill of the city of Playa del Carmen, Mexico

Abstract: Understanding how jaguars (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
10
0
3
Order By: Relevance
“…However, this national park of Maya Biosphere Reserve is prone to anthropogenic disturbances due to its location near the Buffer Zone (García et al 2020; Figure 1). We therefore agree with previous authors that the conservation status of the habitat needs to be evaluated (Morato et al 2016;González-Gallina et al 2017;García et al 2019) as despite Tikal National Park remains with high forest cover but with possible low ecological integrity (García et al 2019;2020).…”
Section: J Ttsupporting
confidence: 92%
“…However, this national park of Maya Biosphere Reserve is prone to anthropogenic disturbances due to its location near the Buffer Zone (García et al 2020; Figure 1). We therefore agree with previous authors that the conservation status of the habitat needs to be evaluated (Morato et al 2016;González-Gallina et al 2017;García et al 2019) as despite Tikal National Park remains with high forest cover but with possible low ecological integrity (García et al 2019;2020).…”
Section: J Ttsupporting
confidence: 92%
“…20,87 Also, jaguars have been shown to greatly decrease space use in highly modified areas with relatively high human population density when supplemental food was available. 88 When placed within the context of our results, these observations illustrate behavioral plasticity by jaguars, and given the extensive retraction in the jaguars' distribution due to anthropogenic factors and the number of threatened populations, 5 highlights the need for additional research to understand jaguars' tolerance of land use and human presence for developing effective conservation actions.…”
Section: Discussionmentioning
confidence: 55%
“…However, conversion of habitat tends to increase the spatial requirements of apex predators, rising conflict with humans 52 , 58 . A recent study that tracked a male jaguar in the vicinity of a city in Mexico reported that the core areas of the jaguar’s home range included a landfill where the jaguar opportunistically predated on dogs, raccoons, and other animals that visited the area 59 . More recently, a male jaguar became famous in Brazil after traveling through different places within a city, including a church, a hotel’s parking lot, industrial neighborhood streets, and the backyard of a residence to feed on chickens, and intervention by environmental agencies was necessary to relocate the individual 60 .…”
Section: Discussionmentioning
confidence: 99%